Effect of Different Grain for Green Approaches on Soil Bacterial Community in a Karst Region - Chen, Huijun; Peng, Wanxia; Du, Hu; Song, Tongqing; Zeng, Fuping; Wang, Feng (Frontiers in Microbiology, 2020)
Soil bacteria participate in nutrient cycling above and below ground to promote ecosystem stability and health. However, the relationship of soil bacteria and environmental factors following the Grain for Green program remains poorly understood in southwest China. Soil samples were collected from seven Grain for Green sites that had been revegetated for 15 years. Four of these sites were afforested with a different tree species: Zenia insignis (ZI), Toona sinensis (TS), Castanea mollissima (CM), and Citrus reticulate (CR). One site was revegetated with Zenia insignis and Guimu-1 elephant grass (ZG), and one with only Guimu-1 elephant grass (GM). The remaining site, abandoned cropland (AC), was left to regenerate naturally. Here, we used Illumina sequencing of 16S rRNA genes to explore how the Grain for Green project affected soil bacterial community. We found that Actinobacteria, Proteobacteria, Chloroflexi, and Acidobacteria were the dominant phyla in these soils. The dominant genera at each revegetation site were also different. The CM, ZI, TS, and AC sites were dominated by Micromonospora, ZG was dominated by Streptomyces, and CR and GM were dominated by Subgroup 6. The bacterial structure was most similar in AC and TS. Correlation analysis showed that the ratio of C:P had positive effects on KD4-96, Intrasporangiaceae, and Gaiella. The ratio of soil N:P was significantly positively correlated with Cupriavidus and Kribbella. The combination of planting Zenia insignis and Guimu-1 elephant grass had the best edaphic benefits, and the approach of planting Citrus reticulate and Toona sinensis needs to be improved. Redundancy analysis revealed that plant Simpson index, and soil N:P contributed to 16% and 15.7% of the total variations in the soil bacterial community composition, respectively. Our results suggested that plant diversity (Shannon-Wiener and Simpson indexes) and soil stoichiometric ratio (N:P) were the important factors affecting the bacterial community, and phosphorus was the limiting factor of the bacterial community in the Grain for Green karst region. In the future, revegetation should be accompanied with phosphorus fertilizer and polycultures should be considered.